A Unique Case of Testicular Compromise in a Patient with Ovotesticular Disorder of Sexual Development and a Solitary Testicle - Ethan Vargo; Lillianne Stanitsas; Mark Memo (Case Reports in Urology)
Ovotesticular disorder of sexual development (OT-DSD), previously true hermaphroditism, is a condition in which one or both gonads contain testicular and ovarian tissue. A 23-year-old OT-DSD male patient presented with continuous pain in his right testicle which had been previously intermittent over the past five days. The patient had a prior history of left ovotestis removal with prosthesis placement, a right undescended testicle with aberrant anatomy, and hypospadias repair, all of which were corrected shortly after birth. A lack of blood flow to the testicle on Doppler ultrasound warranted immediate surgical intervention. Intraoperatively, an aberrant tunica vaginalis space with a compressive hematoma secondary to epididymal abscess rupture was identified as the causation for testicular compromise. Return of vascular flow to the testicle was confirmed with intraoperative Doppler after hematoma and epididymis excision, and the testicle was left in situ. It is imperative to consider epididymal etiologies with acute testicular pain, especially in a patient with a medical history that carries an increased risk for gonadal anomalies.